Reassessing Tax Effort in Developing Countries: a Proposal of a Vulnerability-Adjusted Tax Effort Index (VATEI) - Djedje Hermann Yohou; Michaël Goujon (Fondation pour les études et recherches sur le développement international (FERDI), 2017)
This paper describes the estimation of a new tax effort index for 120 developing countries over 1990-2012. Two major innovations are the use of a new measure of non-resource tax revenues and the correction of the traditional method of tax effort estimation by accounting for structural economic and human vulnerabilities. The results indicate that economic vulnerability is harmful to tax while human asset enhances tax. Moreover, Sub-Saharan African countries exhibit an outstanding vulnerability-adjusted tax effort compared to the other countries.
Keywords: 330; tax effort; economic vulnerability; human assets; non-ressource tax revenue; non-ressource GDP; Developing countries